PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN KUALITAS LABA: APAKAH MEREKA CERMINAN PERILAKU OPORTUNISTIK MANAJER? - Rivi Indriani; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
The purposive of this research is to examine whether the level of Corporate Social Responsibility disclosure (CSRD) influences earnings management in both ordinary companies and export-oriented companies. The independent variable used in the research is Corporate Social Responsibility while the dependent variable in the research is earnings management. In addition, the theory used in this study is stakeholder theory.This research uses regression analysis method with secondary data obtained by purposive sampling method. Research data is secondary data from financial statements and annual reports of manufacturing firm that listed on the Indonesia Stock Exchange in 2017.The results of this research is indicate a positive influence between the level of corporate social responsibility disclosure (CSR) on earnings management in ordinary companies. While for export-oriented companies, there is a negative influence between the level of corporate social responsibility disclosure (CSR) on earnings management.